2020
DOI: 10.1088/1361-6463/ab8138
|View full text |Cite
|
Sign up to set email alerts
|

Broadband microwave metamaterial absorber based on magnetic periodic elements

Abstract: In this paper, we propose and demonstrate a broadband microwave absorber based on magnetic metamaterial structure elements. We deploy FeCo soft magnetic composite with droplet shape as the primary resonant element. By investigating the resonant modes and the coupling between periodic unit-cells and the incident microwave, it is found the intrinsic magnetic susceptibility of the magnetic elements could make the magnetic field confined in the magnetic element, and thus results in a broadband microwave absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Zhuang et al. reported a BMA based on magnetic periodic elements, [ 255 ] the intrinsic magnetization of some magnetic elements could cause the magnetic field to be confined in the magnetic elements, thus leading to broadband microwave absorption.…”
Section: Theoretical Foundations or Principles Of Broadband Metamater...mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhuang et al. reported a BMA based on magnetic periodic elements, [ 255 ] the intrinsic magnetization of some magnetic elements could cause the magnetic field to be confined in the magnetic elements, thus leading to broadband microwave absorption.…”
Section: Theoretical Foundations or Principles Of Broadband Metamater...mentioning
confidence: 99%
“…[253] It is shown that the coupling between overdamped modes had notable advantages in sound absorption, [254] which could exhibit an average sound absorption effect of 81% in the range of 100-1000 Hz. Zhuang et al reported a BMA based on magnetic periodic elements, [255] the intrinsic MAs mainly contain three important but different functional layers: The first (or top) patterned resonator layer for strong interaction with incident beam, the second middle dielectric layer for dissipation of electromagnetic waves, and the third (or bottom) continuous metal layer for blocking the incident waves. Each functional layer plays an essential role in the resonance characteristics of MAs.…”
Section: Coupled Mode Theorymentioning
confidence: 99%
“…Some recent studies have reported that the EAB can be effectively widened using electromagnetic metamaterials. Zhuang et al [ 13 ] proposed a magnetic metamaterial structure based on an FeCo soft magnetic composite with a droplet shape as the primary resonant element; its bandwidth reached 6 GHz. The droplet‐shaped units formed by the metal mold were periodically arranged and pasted onto the FR‐4 substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40][41][42][43][44] Incorporating traditional MAMs into nonmetal-based metamaterial design has yielded significant results. Notably, carbon-based [45][46][47][48][49] and magnetic materials [50][51][52][53][54][55][56][57][58] have been ingeniously employed as fundamental building blocks for nonmetal-based MMAs, showcasing exceptional broadband performances.…”
Section: Introductionmentioning
confidence: 99%